Pancreatic cysts: Not always Cystadenoma - Alba Manuel Vázquez; Latorre Fragua R; de la Plaza R; Ramia JM (Annals of Pancreatic Disorders and Treatment - Peertechz Publications, 2018)
Pancreatic neuroendocrine tumors (PNETs) account for 1-5% of all pancreatic neoplasms and are typically solid in nature. Only about 10% of are cystic [1-3]. One of the challenges in their management is establishing an accurate preoperative diagnosis.